Population trends and distribution of equines in India - Rahul Behl,; PK Vij,; Jyotsna Behl,; Arjava Sharma, (Journal of Livestock Biodiversity, 2025)
Donkeys, mules and horses are important animal genetic resources of India, used mainly for transportation in dif~icult areas. Present status of these species was evaluated in terms of their population trend and distribution. It is estimated that by 2027, the population of donkeys, mules and horses may decline to mere 1.36, 1.93 and 4.78 lakhs, respectively. Only eleven states in India have more than 5000 donkeys, whereas, only nine states have more than 5000 mules. Further, the populations of these species are now restricted to a few regions only. Fifty-two percent of the population of horses of the Karnataka state is now confined to the two districts of Belgaum and Bijapur. These results suggest that these species require immediate attention for their conservation and propagation.